2016
DOI: 10.1016/j.aogh.2016.04.041
|View full text |Cite
|
Sign up to set email alerts
|

What do healthcare providers know about human papillomavirus (HPV) and cervical cancer? a cross-sectional knowledge assessment in Debre Markos, Ethiopia

Abstract: Background: Cervical cancer is the most common cancer among women living in sub-Saharan Africa. Ethiopia has a high incidence of cervical cancer (35.9 per 100,000 women), with 7,095 women diagnosed annually and 4,732 dying every year from the disease. Low provider awareness and poor understanding of appropriate prevention, treatment, and screening interventions pose challenges to addressing this problem. To gauge the extent of this information gap, the study explores variation in healthcare providers' knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, as other studies in low-income settings have found provider knowledge of cervical cancer screening and treatment best practice is patchy, particularly for mid-level providers [ 17 , 24 , 28 , 30 , 50 54 ]. For example, an internal evaluation in 2015 that we conducted at Debre Markos Referral Hospital (one of the facilities sampled in this study) found that knowledge of different screening and treatment procedures was inconsistent and varied significantly by profession with only 57% of respondents in able to identify cryotherapy as a treatment method, and only 48% of nurses able to identify VIA as a screening method, even though these are recommended practices in Ethiopia [ 29 ]. Almost 40% of nurses and midwives in that evaluation were not able to identify vaginal discharge as a symptom of cervical cancer; one-third could not identify abdominal pain, and almost 70% of all midlevel providers were not aware that cervical cancer could be asymptomatic [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as other studies in low-income settings have found provider knowledge of cervical cancer screening and treatment best practice is patchy, particularly for mid-level providers [ 17 , 24 , 28 , 30 , 50 54 ]. For example, an internal evaluation in 2015 that we conducted at Debre Markos Referral Hospital (one of the facilities sampled in this study) found that knowledge of different screening and treatment procedures was inconsistent and varied significantly by profession with only 57% of respondents in able to identify cryotherapy as a treatment method, and only 48% of nurses able to identify VIA as a screening method, even though these are recommended practices in Ethiopia [ 29 ]. Almost 40% of nurses and midwives in that evaluation were not able to identify vaginal discharge as a symptom of cervical cancer; one-third could not identify abdominal pain, and almost 70% of all midlevel providers were not aware that cervical cancer could be asymptomatic [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, an internal evaluation in 2015 that we conducted at Debre Markos Referral Hospital (one of the facilities sampled in this study) found that knowledge of different screening and treatment procedures was inconsistent and varied significantly by profession with only 57% of respondents in able to identify cryotherapy as a treatment method, and only 48% of nurses able to identify VIA as a screening method, even though these are recommended practices in Ethiopia [ 29 ]. Almost 40% of nurses and midwives in that evaluation were not able to identify vaginal discharge as a symptom of cervical cancer; one-third could not identify abdominal pain, and almost 70% of all midlevel providers were not aware that cervical cancer could be asymptomatic [ 29 ]. Providers’ poor knowledge of symptoms and lack of knowledge of appropriate protocols may explain why so many of the women in our sample were initially misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation